Tapping the Potential for Energy Savings in Turkey - World Bank (Washington, DC, 2013)
This report, Tapping the Potential for Energy Savings in Turkey, focuses on sector and analytical work to assess demand-side energy efficiency measures that require specific attention in Turkey. The report provides recommendations on potential government strategies to promote energy efficiency and to scale up investments. The report concludes that the Government now needs to be focused on creating the enabling environment to develop an energy efficiency market and incentives as well as rules and standards for private sector capital and technical capacity to prioritize energy efficiency. National and sector targets for energy savings may be set to clarify the Government's intent to improve energy efficiency. Specific actions and policy recommendations are addressed.